Analisis Sentimen Terhadap Program Kampanye Desak Anies Di X Menggunakan Naïve Bayes - Dimas Arya; Ilka Zufria (STMIK Budi Darma, 2024)
Information technology provides many influences including political, economic, artistic, cultural, social and educational. In 2023 the number of internet users in Indonesia will reach 215.63 million. This increase shows how important social media platforms like X are in public discussions. All attention is focused on political campaigns ahead of the Indonesian presidential election in 2024. This research was conducted to determine public sentiment towards two-way campaigns such as